Bridging Health Disparity Gaps through the Use of Medical Legal Partnerships in Patient Care: A Systematic Review. Issue 2 (June 2017) - Martinez, Omar; Boles, Jeffrey; Muñoz-Laboy, Miguel; Levine, Ethan C.; Ayamele, Chukwuemeka; Eisenberg, Rebecca; Manusov, Justin; Draine, Jeffrey
Over the past two decades, we have seen an increase in the use of medical-legal partnerships (MLPs) in health-care and/or legal settings to address health disparities affecting vulnerable populations. MLPs increase medical teams' capacity to address social and environmental threats to patients' health, such as unsafe housing conditions, through partnership with legal professionals. Following the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines, we systematically reviewed observational studies published from January 1993-January 2016 to investigate the capacity of MLPs to address legal and health disparities. We identified 13 articles for qualitative analysis from an initial pool of 355 records. The resulting pool of 13 articles revealed more information regarding the capacity of MLPs to address legal outcomes than their capacity to address health outcomes; only 4 studies directly addressed the impact of MLP intervention on patient wellbeing and/or patient utilization of healthcare services. We call for further evaluation/longitudinal studies that specifically address MLPs' short and long term effects upon patient health disparities. Finally, given the demonstrated capacity of MLPs to address unmet legal needs, and their evident potential in regards to improving health outcomes, we present the MLP model as a framework to address HIV-related legal and health disparities.